Navigating the Management of Assets, Facilities, and Financial Strategies to Ensure Business Continuity in Ageing Buildings in the Klang Valley, Malaysia - Mohd Marzuki, Mohd Mazhar (2025)
Ageing buildings, particularly in the Klang Valley, Malaysia, threatens business continuity and financial performance. These under-managed assets pose major risks, including disruption of operations, increased costs, and deterioration of competitiveness, while emphasising the strategic importance of proactive management. However, existing literature tends to discuss asset management, facilities management and financial planning in isolation, emphasising the need for a unified approach. In light of this challenge, this study aims to explore how strategic asset and facilities management, supported by solid financial planning principles such as life cycle costing, can effectively sustain business continuity and foster organisational resilience. Guided by the theoretical framework, this research utilises a qualitative methodology. A semi-structured interview was conducted with professionals involved in the management of ageing buildings, and the data were analysed thematically to identify common practices, strategic gaps and implementation challenges, before it reaches data saturation at the 11th Informant. The findings show that proactive asset management and integrated financial planning through life cycle costing are critical to minimise operating disruptions and long-term costs, yet their efficacy is often hindered by budgetary constraints, lack of management support and commitment, and insufficient asset data. In response, this study proposes a new integrated strategic management framework, presented as a Body of Knowledge (BOK), that systematically links asset management, facilities management and financial planning to improve business continuity, operating efficiency and cost effectiveness in ageing buildings. The framework advances scientific understanding by bringing together previously separate domains and demonstrating the important link between physical asset management and sustainable business performance. At the same time, it provides business leaders, facilities managers and policy makers with actionable guidelines to maintain competitive advantage and operational resilience in the face of ageing infrastructure.